2020
DOI: 10.21009/biosferjpb.v13n2.201-215
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of potentially “lalapan” vegetables in Kampung Adat Naga, Tasikmalaya, Indonesia

Abstract: Kampung Naga is a traditional village or ethnic in Tasikmalaya, Indonesia with a wealth of biodiversity. This ethnic group, with local knowledge, always involves natural richness in everyday life (ethnobotany). However, not many know about utilizing potentially lalapan vegetables that are commonly used daily by the indigenous people of Kampung Naga. Therefore, this research aims to describe the diversity of potentially lalapan vegetables in the ethnobotanical study used by the people of Kampung Adat Naga. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This result is slightly similar to other studies in West Java areas, including the Subang Sub-district (Cahyanto et al 2019) and Naga Community of Tasikmala (Septiani et al 2020) in that it has several families, namely Fabaceae has a high number of species. Some species of Family Fabaceae, namely Archidendron jiringa (Jack) I.C.…”
Section: Local Knowledge Of Vegetable Plantssupporting
confidence: 90%
See 2 more Smart Citations
“…This result is slightly similar to other studies in West Java areas, including the Subang Sub-district (Cahyanto et al 2019) and Naga Community of Tasikmala (Septiani et al 2020) in that it has several families, namely Fabaceae has a high number of species. Some species of Family Fabaceae, namely Archidendron jiringa (Jack) I.C.…”
Section: Local Knowledge Of Vegetable Plantssupporting
confidence: 90%
“…The level of vegetable diversity in Cijambu Village is considerably high compared to that recorded in Kampung Naga, Tasikmalaya, which only has 46 species representing 22 families (Septiani et al 2020) with species from the Fabaceae family as the dominant family, slightly lower than that found in Subang district with 50 species representing 19 families. However, it has almost the same number of species from the Fabaceae family (Cahyanto et al 2019)…”
Section: Part Usedmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition to growing wild, these plants are typically consumed as fresh vegetables. The Sundanese (Septiani et al 2020) and Batak (Ayu et al 2020) have used the raw fruit of S. nigrum as fresh vegetables. However, Albouchi et al (2018) indicated that the S. nigrum, in some parts, can be toxic to humans, therefore it is suggested to consume ripe fruit and cooked leaves.…”
Section: Food Plantsmentioning
confidence: 99%
“…Lalapan can be consumed fresh, such as kubis (Brassica oleracea), selada (Nasturtium officinale), kenikir (Cosmos caudatus), terong (S. melongena), mentimun (Cucumis sativus), and kemangi (Ocimum bacilicum). Cooked vegetable species include bayam (Amaranthus hybridus), leunca (S. nigrum), kangkung (Ipomoea aquatica), and daun genjer (Limnocharis flava), which are often included in vegetable soup, stir-fried, and pickle (Septiani et al 2020). Amrinanto et al (2019) stated that consuming lalapan can increase blood β-carotene.…”
Section: Processing Methods For Consumptionmentioning
confidence: 99%